Human amniocyte‐derived cells are a promising cell host for adenoviral vector production under serum‐free conditions. Issue 5 (May 2015) - Silva, Ana Carina; Simão, Daniel; Küppers, Claudia; Lucas, Tanja; Sousa, Marcos F. Q.; Cruz, Pedro; Carrondo, Manuel J. T.; Kochanek, Stefan; Alves, Paula M.
Abstract Recombinant adenovirus vectors (AdVs) have been used for the development of vaccines, as gene therapy vectors and for protein production. Currently, the production of clinical grade batches of recombinant E1‐deleted adenovirus type 5 vectors is performed using human‐derived HEK293 or PER.C6® cell lines. In this work we describe the generation of a new human amniocyte‐derived cell line named 1G3 and show that it can be used as a very promising cell host for AdV production in serum‐free conditions, allowing for production in high cell density cultures and avoiding the typical cell density effect observed for HEK293. By design, this cell line makes the generation of replication‐competent adenovirus during production of E1‐deleted AdVs very unlikely. The impact of the culture system (static versus agitated) and AdV infection parameters such as multiplicity of infection, time of harvesting and cell concentration at infection were evaluated and compared with HEK293. Using stirred tanks bioreactors, it was possible to grow 1G3 cells to cell densities of up to 9 × 106 cells/mL using serum‐free media. Moreover, without a medium exchange step at infection, a three‐fold increase in AdV volumetric titers was obtained, as no cell density effect was observed at CCI 3. Overall, our results clearly demonstrate the potential of the human amniocyte‐derived newly established cell line 1G3 for AdV production in a serum‐free scalable process, paving the way for further process improvements based on fed‐batch or perfusion strategies.